Isolation of a molybdenum--iron cluster from nitrogenase. - Shah, V K (1981)
A molybdenum-iron cluster (Mo-Fe cluster) containing 6 Fe atoms per Mo was isolated by methyl ethyl ketone extraction of component I of nitrogenase from Azotobacter vinelandii. The cluster has no EPR signal in the g = 4 region but has an intense signal at g = 2.05 and 2.01. After the cluster was transferred from methyl ethyl ketone to N-methylformamide, the signal in the g = 2 region disappeared and a signal similar to that found with Fe-Mo cofactor appeared. The Mo-Fe cluster is the EPR-active center that undergoes reversible oxidation-reduction during catalytic turnover at the active site of the enzyme. In contrast to the Fe-Mo cofactor, which contains 8 Fe atoms per Mo, the Mo-Fe cluster failed to activate either inactive component I in extracts of A. vinelandii mutant strain UW45 or tungsten-containing component I from wild-type A. vinelandii. On the other hand, the Mo-Fe cluster showed as much acetylene-reduction activity with sodium borohydride as the reductant as did the Fe-Mo cofactor. Like nitrogenase-dependent and Fe-Mo cofactor-dependent acetylene reduction, the Mo-Fe cluster-dependent acetylene reduction is strongly inhibited by carbon monoxide.